Detection of TP53 mutation using a portable Surface Plasmon Resonance DNA-based biosensor - Jiang, Tieshan; Minunni, Maria E.; Wilson, P. K.; Zhang, Jian; Turner, Anthony P. F.; Mascini, Marco (Elsevier, 2005)
A DNA-based Surface Plasmon Resonance (SPR) biosensor has been developed for the detection of TP53 mutation using the inexpensive and commercially available instrument, SPREETATM SPR-EVM-BT, from Texas Instruments. A direct immobilization procedure, based on the coupling of thiol-derivatised oligonucleotide probes (Probe-C6-SH) to bare gold sensor surfaces, was optimized using synthetic oligonucleotides. Hybridization reactions between the immobilized probe and a short sequence (26 mer) complementary, non-complementary and one point mutation DNA were then investigated. The main analytical parameters of the sensor system were studied in detail including selectivity, sensitivity, reproducibility and analysis time. Finally, the sensor system was successfully applied to polymerase chain reaction (PCR) amplified real samples, DNA extracted from both normal, wild type, (Jurkat) and mutated (Molt 4), carrying the mutation at codon 248 of the TP53 cell lines. The results obtained demonstrate that the DNA-based SPR biosensor was able to distinguish sequences present in the various samples that differ only by one base and hence it appears to be a strong candidate technique for the detection of gene mutation.